RETRACTED: Ahmad et al. Quantification and Evaluations of Catechin Hydrate Polymeric Nanoparticles Used in Brain Targeting for the Treatment of Epilepsy. Pharmaceutics 2020, 12, 203 - Niyaz Ahmad; Rizwan Ahmad; Ridha Abdullah Alrasheed; Hassan Mohammed Ali Almatar; Abdullah Sami Al-Ramadan; Mohd Amir; Md Sarafroz (Pharmaceutics, 2025)
The journal retracts the article “Quantification and Evaluations of Catechin Hydrate Polymeric Nanoparticles Used in Brain Targeting for the Treatment of Epilepsy” [...]